Square Slot Antenna for Wide Circularly Polarized Bandwidth and Axial Ratio Beamwidth - Sharma Vijay; Jhajharia Tejpal (Electrical, Control and Communication Engineering)
The article proposes design investigation and experimental results of a coplanar waveguide (CPW) fed square slot antenna that gives wideband circular polarization. This circular polarization characteristic is achieved by embedding a square shape stub to left bottom corner and an L-shaped strip to the right upper corner of the slot. A high impedance bandwidth of 87.8 % (3.6–9.0 GHz), a wide axial ratio bandwidth of 73.05 % (4.2–9.0 GHz) and wide 3-dB axial ratio beamwidth of 90° in the entire frequency range of interest are achieved with this antenna structure. To improve the 3-dB axial ratio bandwidth, three slots (two horizontal and one vertical) are scratched at the exterior periphery of the ground plane. These perturbation assemblies are accountable to excite orthogonal modes and help increase an axial ratio bandwidth. The designed antenna displays the constant and steady radiation patterns in the complete frequency range of concern. The overall dimension of the presented compact antenna is 0.24λ × 0.24λ × 0.01λ.